Genetic architecture of age-related cognitive decline in African Americans. (February 2017) - Raj, Towfique; Chibnik, Lori B.; McCabe, Cristin; Wong, Andus; Replogle, Joseph M.; Yu, Lei; Gao, Sujuan; Unverzagt, Frederick W.; Stranger, Barbara; Murrell, Jill; Barnes, Lisa; Hendrie, Hugh C.; et al.
Abstract : Objective: To identify genetic risk factors associated with susceptibility to age-related cognitive decline in African Americans (AAs). Methods: We performed a genome-wide association study (GWAS) and an admixture-mapping scan in 3, 964 older AAs from 5 longitudinal cohorts; for each participant, we calculated a slope of an individual's global cognitive change from neuropsychological evaluations. We also performed a pathway-based analysis of the age-related cognitive decline GWAS. Results: We found no evidence to support the existence of a genomic region which has a strongly different contribution to age-related cognitive decline in African and European genomes. Known Alzheimer disease (AD) susceptibility variants in the ABCA7 and MS4A loci do influence this trait in AAs. Of interest, our pathway-based analyses returned statistically significant results highlighting a shared risk from lipid/metabolism and protein tyrosine signaling pathways between cognitive decline and AD, but the role of inflammatory pathways is polarized, being limited to AD susceptibility. Conclusions: The genetic architecture of aging-related cognitive in AA individuals is largely similar to that of individuals of European descent. In both populations, we note a surprising lack of enrichment for immune pathways in the genetic risk for cognitive decline, despite strong enrichment of these pathways among genetic risk factors for AD.